A 6-week coordinative motor training program improves spatial ability performances in healthy children - Morawietz, Christina; Wissmann, Anna Maria; Muehlbauer, Thomas (Frontiers in Cognition, 2024)
Background: With overall academic achievements decreasing, policies tend to dedicate more curricular time to other subjects than physical education (PE). In light of increasingly sedentary lifestyles and rises in levels of overweight and obesity, this trend is detrimental within the global health context. Simultaneously, research on the connection between physical activity, cognitive functions, and academic achievement is on the rise. Cognitive functions like good spatial abilities have frequently been associated with higher achievements in STEM-subjects.This study is aimed to investigate the effects of a six-week coordinative motor training with spatial elements on spatial ability performances in healthy children.: Fifty-three children (mean age ± SD; 11.3 ± 0.6 years; 30 girls) participated in either a six-week coordinative motor training (i.e., intervention group; 2x/week, 45 min/session) or attended regular PE class using the same volume (i.e., control group). Spatial abilities before and after the intervention period were evaluated in both groups using the Paper Folding Test (PFT), Mental Rotation Test (MRT), Water Level Task (WLT), Corsi Block Test (CBT), and Numbered Cones Run (NCR).Results: No significant differences between groups were observed at baseline. A main effect of test but not of group was found for all variables. For all but one test (i.e., PFT), a significant test × group interaction was detected. Post-hoc analyses revealed significant medium-to largesized improvements from pre-to posttest in the intervention but not in the control group.The results indicate that a six-week coordinative motor training with spatial elements is feasible in school-aged children and positively affects their spatial abilities.